2020
DOI: 10.1002/app.50096
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of epoxy thermosets with nano‐sized or micron‐sized domains of poly(ethylene oxide)‐b‐poly(butadiene‐co‐acrylonitrile)‐b‐poly(ethylene oxide) triblock copolymers synthesized using room temperature ester coupling reaction

Abstract: Poly(ethylene oxide)-b-poly(butadiene-co-acrylonitrile)-b-poly(ethylene oxide) (PEO-b-PBN-b-PEO) triblock copolymers with three different compositions were synthesized from poly(ethylene glycol) methyl ethers and carboxylic acid-terminated poly(butadiene-co-acrylonitrile) (CTBN) by ester coupling reaction at room temperature. The PEO-b-PBN-b-PEO was incorporated into anhydride cured epoxy thermosets to improve the fracture toughness by the formation of either nano-sized spherical micelles or micron-sized vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…As shown in Figure 8, during the fracture process, the dispersed phase can induce shear deformation of the matrix. Additionally, microcracking and crack deflection caused by the island phase can improve fracture toughness [34,36,43]. Further analysis of the fracture surface of the carboxyl-terminated BCP system showed that after the crosslinking and curing reactions, a significant number of island- phase structures of different sizes were distributed in the epoxy resin matrix.…”
Section: Fracture Surface Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 8, during the fracture process, the dispersed phase can induce shear deformation of the matrix. Additionally, microcracking and crack deflection caused by the island phase can improve fracture toughness [34,36,43]. Further analysis of the fracture surface of the carboxyl-terminated BCP system showed that after the crosslinking and curing reactions, a significant number of island- phase structures of different sizes were distributed in the epoxy resin matrix.…”
Section: Fracture Surface Analysismentioning
confidence: 99%
“…As shown in Figure 8, during the fracture process, the dispersed phase can induce shear deformation of the matrix. Additionally, microcracking and crack deflection caused by the island phase can improve fracture toughness [34,36,43]. A comparison of the fracture surface results (Figure 9) at room and high temperatures showed that the main difference was that the matrix exhibited more bulk deformation during high-temperature testing at low magnification.…”
Section: Fracture Surface Analysismentioning
confidence: 99%
See 1 more Smart Citation